Magnetohydrodynamic effects in mixed convection of ferrofluid flow at lower stagnation point on horizontal circular cylinder - Siti Hanani, Mat Yasin; Muhammad Khairul Anuar, Mohamed; Zulkhibri, Ismail; Mohd Zuki, Salleh (Akademi Baru, 2021)
In this paper, mixed convection of ferrofluid containing magnetite, Fe3O4 with ferroparticles suspended in water at the lower stagnation point on a horizontal circular cylinder is investigated. The partial differential equation which derived from the transformation of the dimensional governing equation and non-similarity transformation with the consideration of the effect of magnetohydrodynamic (MHD) are solved numerically by using Keller-box method. The influences of an external magnetic field on ferrofluid flow and heat transfer are then discussed. The results showed that the viscosity depends on the ferroparticle volume fraction and ferrofluid temperature. The uniform magnetic field that produced Lorentz force acts as a determiner of the trend of fluid movement and has the tendency to control the cooling rate of the surface.